Prioritizing BIM Capabilities of an Organization: An Interpretive Structural Modeling Analysis. (2017) - Ahuja, Ritu; Sawhney, Anil; Arif, Mohammed
Abstract: The Indian Architectural Engineering and Construction sector is grappling with the adoption of BIM as is evident from a relatively low level of adoption. While there have been sufficient number of successful (and unsuccessful) project level implementations of BIM in India, the maturity level of the overall industry and its constituents remains relatively low. One of the challenges faced, especially at the organizational level, is an understanding and development of the organization's BIM capabilities. These capabilities need attention in terms of their effectiveness and hierarchy of implementation in order to overcome the challenges of adoption and increasing maturity levels in BIM usage. The inability to identify crucial BIM capabilities is one of the primary barriers to ineffective BIM implementation and slow adoption in India. The aim of this study is to investigate the dynamics of different BIM capabilities and to understand how these capabilities can be represented as a set of interrelated elements by adopting Interpretive Structure Modeling (ISM) technique Accordingly, a clear understanding regarding the nature of each BIM capability is developed that will help the organizations to plan the strategic implementation of BIM on any project and gain systematic, logical and productive results. Through the three-phased study, it was concluded that BIM capabilities namely visualization, energy and environment analysis, structural analysis, MEP system modelling, constructability analysis, and BIM for as-built were found to be the independent BIM capabilities having strong driving power but weak dependence power. Facilities management is a dependent BIM capability with weak driving power but strong dependence power. This study provides a roadmap to BIM implementers by highlighting the driving and dependence power of each BIM capability which is deemed useful for enhanced delivery of construction projects. Significant theoretical and practical implications are envisioned for both researchers and project managers through the findings of this study.